Application of the R2D2 Model for Active Learning Strategy in Graduate Midwifery Course (International Journal of Nursing Education, 2019)
Background: Active learning strategy is considered an effective method to improve learning outcomes. The R2D2 model is proposed as a framework to promote student engagement in learning process. Purpose: This study aimed to examine the application of read, reflect, display and do model (R2D2) to promote active learning in advanced Midwifery on course pathophysiology and pharmacology. Methodology: A descriptive qualitative research was employed. The study setting was the graduate program of Faculty of Nursing, Prince of Songkla University, Thailand. Six graduate nursing students were approached and recruited as informants. Four steps of teaching and learning activities were implemented: 1) select course contents were assigned as online reading assignment, 2) reflective writing based on the reading assignment, 3) concept mapping to summarize essential ideas, and 4) in-class and online presentation of learned activities. Learning outcomes and students’ responses were evaluated. Data were collected using in-depth interviews. Content analysis was conducted to analyzed qualitative data. Results: Achievement of desired learning outcomes was the results of application of the R2D2 model. Four themes emerged: 1) intending to read, 2) reflecting challenge, 3) displaying creatively, and 4) doing it interestingly. Conclusion: Findings showed that the students achieved good learning experiences and were satisfied with these learning activities. This teaching model can be used to encourage constructive knowledge among graduate students.